Penggolongan Anak Berkebutuhan Khusus Berdasarkan Mental Emosional Dan Akademik - Susi Saswita; Cory Octavia; Ahamad Pauzan Hermandi; Opi Andriani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Children with special needs are children who require special treatment because of developmental disorders and abnormalities experienced by children. Children with special needs have differences that occur in several ways, such as the process of growth and development that experiences abnormalities or deviations both physically, mentally, intellectually, socially and emotionally. In the context of special education in Indonesia, children with special needs are categorized in terms of blind children, deaf children, children with intellectual disabilities, children with motor disabilities, children with social emotional disorders, and children with intelligent and special talents. Every child with special needs has different characteristics from one to another. In addition, every child with special needs also needs special services that are tailored to their abilities and characteristics. It is important to carry out identification and assessment activities to identify their characteristics and needs. It is considered important to get the right service according to the characteristics, needs and capabilities.